The optimal e-commerce sales mode selection and information sharing strategy under demand uncertainty. (December 2021) - Yang, Man; Zhang, Tao; Wang, Chuan-xu
Highlights: The e-commerce sales mode and information sharing are considered. Manufacturer's investment efficiency affects parties' sales mode selection. Information sharing strategy affects parties' sales mode preferences. E-retailer's prediction accuracy affects both parties' optimal decisions. Players can benefit from more accurate prediction information. Abstract: Demand forecasting is important information for all enterprises. Accurate forecast information determines the success of supply chain operations. This paper studies the selection strategy of e-commerce sales mode and information sharing strategy in a dual-channel supply chain. The manufacturer and e-retailer enter a Stackelberg competition. The e-retailer independently decides to share or not share forecasting demand information to the manufacturer. The results show that only if the investment efficiency of the manufacturer's after-sales service is high, e-retailer is willing to share demand forecasting information. Information sharing does not always add value to the e-retailer, which may lead to the 'precision trap' of the e-retailer. Moreover, forecasting accuracy always has a positive impact on the e-retailer's profit. However, the manufacturer would benefit from more accurate forecasting demand in the case of sharing information. Otherwise, prediction accuracy is negatively correlated with the manufacturer's profit. Besides, the selection strategy of e-commerce sales mode depends on the level of the manufacturer's investment efficiency. Specifically, if the manufacturer invests in after-sales service more efficiently, platform sales mode is preferred. If not, they prefer wholesale sales mode.